Direct Calibration Method for LA-HR-ICP-MS Apatite U-Pb Dating - ZHAO Linghao; ZHAN Xiuchun; ZENG Lingsen; HU Mingyue; SUN Dongyang; YUAN Jihai (Yankuang ceshi, 2022)
BACKGROUND Apatite is a common U-bearing accessory mineral with a U-Pb closure temperature of ~500℃, making U-Pb dating of apatite a potentially valuable thermochronometer. However, its low U concentration, high common lead concentration and lack of reference material has limited widespread application to LA-ICP-MS dating. OBJECTIVES To develop a technique for U-Pb dating of apatite using laser ablation sector field inductively coupled plasma-mass spectrometry (LA-HR-ICP-MS). METHODS The U-Pb isotope ratio in apatite samples was determined by LA-HR-ICP-MS, with apatite MAD2 as the external standard to correct U-Pb and Pb-Pb elemental fractionation directly without a common Pb correction. RESULTS Long-term U-Pb analysis of Madagascar apatite sample (MAD2) showed homogeneous distribution of U, Pb and U-Pb isotope ratios, with average contents of U and Pb ~23.8×10-6 and ~13.5×10-6, respectively and weighted average 207Pb/206Pb and 206Pb/238U ratios of 0.0941±0.0006 and 0.0794±0.0004, respectively. Taking MAD2 apatite as a reference mineral, combined with 207Pb-correction method, the ages of apatite samples, McClure Mountain (521±5Ma), Tory-Hill-apt (1021±16Ma), a Durango (30.7±1.5Ma) and Fagnshan diorite apatite (~131Ma) can be determined accurately. CONCLUSIONS The Madagascar apatite sample (MAD2) can be used to calibrate apatite U-Pb isotope ratio measured by LA-ICP-MS directly, without common-Pb correction, similar to the calibration strategy in zircon U-Pb dating. The method greatly reduces the difficulty of data processing during apatite U-Pb dating by LA-ICP-MS, which is conducive to the wide application of the method.